2018
DOI: 10.3389/fmicb.2018.02944
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Recombinant Lentinula edodes Xylanase by Pichia pastoris and Its Effects on Ruminal Fermentation and Microbial Community in in vitro Incubation of Agricultural Straws

Abstract: Agricultural straws, such as rice straw, wheat straw, and corn straw, are produced abundantly every year but not utilized efficiently in China. An experiment was conducted to determine the effects of recombinant xylanase on ruminal fermentation and microbial community structure in in vitro incubation of these straws. The recombinant xylanase from Lentinula edodes (rLeXyn11A) was produced in Pichia pastoris. The optimal temperature and pH for rLeXyn11A were 40°C and 4.0, respectively. The rLeXyn11A featured res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 59 publications
3
23
0
Order By: Relevance
“…In the current study, the dominant VFA product of ruminal fermentation from dairy goats in the Lp A1 and Lp MTD/1 treatments was acetate. The greater concentration and molar rate of acetate in Lp A1 treatment indicated that the efficiency of rumen fermentation for the diet was greater in the Lp A1 treatment than in the control (Lp MTD/1 treatment) ( Li et al., 2018 ). Moreover, there was no difference in the ratio of acetate to propionate between the 2 treatment groups, which might be related to the consistency of the composition of the 2 experimental diets ( Fimbres et al., 2002 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, the dominant VFA product of ruminal fermentation from dairy goats in the Lp A1 and Lp MTD/1 treatments was acetate. The greater concentration and molar rate of acetate in Lp A1 treatment indicated that the efficiency of rumen fermentation for the diet was greater in the Lp A1 treatment than in the control (Lp MTD/1 treatment) ( Li et al., 2018 ). Moreover, there was no difference in the ratio of acetate to propionate between the 2 treatment groups, which might be related to the consistency of the composition of the 2 experimental diets ( Fimbres et al., 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…About 250 g/L (wt/vol) HPO 3 was mixed with ruminal fluid at a ratio of 1:5 and left overnight at 4 °C for the precipitation of true proteins. After centrifugation (4 °C; 15,000 ✕ g ; 15 min) and filtration with an 0.22-μm dialyzer, the VFA concentration of ruminal fluid was determined by a gas chromatograph (SP-3420A, Beijing Beifen-Ruili Analytical Instrument Co., Ltd, Beijing, China) that equipped with an AT-FFAP type capillary column (30 m × 0.32 mm × 0.5 μm) and a Flame Ionization Detector ( Li et al., 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Members of the genus Acetobacter are important obligate anaerobes capable of both degrading readily fermentable carbohydrates and over‐oxidizing ethanol produced by Klebsiella to acetic acid (Kadere et al, 2008). Similarly, the fungal genus Pichia has a potential probiotic effect on cattle and can stimulate greater VFA potential (Fernandes et al, 2019); supplementation of recombinant xylanase produced by Pichia pastoris increased fibre digestibility, acetate concentration, total VFA production and microbial protein content (Li et al, 2018). The above results thus explain Acetobacter's significant positive correlations with Pichia , Klebsiella and Acinetobacter observed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Although this agricultural straw fiber can be decomposed with ruminal microbiota, their ruminal degradability is still relatively low [7]. To enhance this straw fiber digestibility in rumen, adding exogenous fibrolytic enzymes (EFEs) with ruminant diets has been widely studied [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…cazy. org), including GH5 to 10,12,26,44,45,48,51,60,61,74,124 and 131 [11]. Among these, GH5 is the largest family, and most of the GH5 cellulases are endoglucanases [11,12].…”
Section: Introductionmentioning
confidence: 99%